2003
DOI: 10.1002/cne.10898
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of the norepinephrine transporter in superficial and deep layers of the rat prelimbic prefrontal cortex and its spatial relationship to probable dopamine terminals

Abstract: The prefrontal cortex (PFC) is a likely site of action for the therapeutic efficacy of antidepressants that inhibit norepinephrine (NE) reuptake. Moreover, drugs that block the NE transporter (NET) increase extracellular levels of both NE and dopamine (DA), an interaction that may contribute to their therapeutic properties. To examine the subcellular localization of NET and to investigate the spatial relationships between presumed NE and DA axons within the rat prelimbic PFC, we combined immunogold-silver loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
97
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 96 publications
22
97
1
2
Order By: Relevance
“…Thus, b2-AR appears to play a distinct role in memory processing via coupling with different downstream signaling, although the mechanism responsible for the recruitment of different signaling by b2-AR is unknown. In the PFC, noradrenergic fibers originating from the brain stem target both deep and superficial layers of the cortex (Lewis and Morrison 1989;Miner et al 2003). Synaptic plasticity occurring in superficial layer 2/3 pyramidal cells of the cortex has been proposed to correspond to the trace fear conditioning (Wu et al 2008;Descalzi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, b2-AR appears to play a distinct role in memory processing via coupling with different downstream signaling, although the mechanism responsible for the recruitment of different signaling by b2-AR is unknown. In the PFC, noradrenergic fibers originating from the brain stem target both deep and superficial layers of the cortex (Lewis and Morrison 1989;Miner et al 2003). Synaptic plasticity occurring in superficial layer 2/3 pyramidal cells of the cortex has been proposed to correspond to the trace fear conditioning (Wu et al 2008;Descalzi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans, non-human primates, and rats have shown that the PFC receives catecholaminergic inputs from the midbrain (Porrino and Goldman-Rakic, 1982;Levitt et al, 1984;Lewis et al, 1987;Lewis and Morrison, 1989;Miner et al, 2003) and a substantial amount of data supports the conclusion that dopamine (DA) and noradrenaline (NE) are involved in aspects of executive function (selective attention, response selection/control), as well as arousal (NE). These actions of DA and NE have been postulated to occur via their effects in the cortex.…”
Section: Introductionmentioning
confidence: 90%
“…Varicosities represent sites where neurotransmitter synthesis, packaging, release, and reuptake most often occur (Benes et al, 1996). Furthermore, we and others have shown that the TH antibody used in these studies labels dopamine axons but rarely labels norepinephrine axons within the regions of interest (Miner et al, 2003;Manitt et al, 2011Manitt et al, , 2013. As in all our previous neuroanatomical studies, we obtained counts only from the right hemisphere because of the lateralization of dopamine systems.…”
Section: Neuroanatomical Analysismentioning
confidence: 99%